2014
DOI: 10.1159/000358922
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complications of the Suprameatal Approach and Mastoidectomy with Posterior Tympanotomy Approach in Cochlear Implantation: A Meta-Analysis

Abstract: Background: Cochlear implantation (CI) is a popular procedure to preserve hearing in patients with severe-to-profound hearing loss. Evidence shows that the suprameatal approach (SMA) may help reducing the risk of the incidence of complications and shortening the surgery time, but there is still dispute. Objectives: The aim of this study was to compare the incidence of complications of SMA and the mastoidectomy with posterior tympanotomy approach (MPTA), and to find whether SMA yields better outcomes than MPTA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The rate of device failure was 2%; therefore, the unwanted outcomes requiring surgery were 4.66%, while 10% reported minor complication rate. 19 Xu et al, 20 in a meta-analysis study of 799 cases, reported no statistically significant difference in major and minor complications between the two approaches, except for facial nerve and chorda tympani injuries, favoring SMA. 20 Migirov et al 21 operated 300 cases of CI and reported a rate of 3% major complications and 25.7% minor complications.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rate of device failure was 2%; therefore, the unwanted outcomes requiring surgery were 4.66%, while 10% reported minor complication rate. 19 Xu et al, 20 in a meta-analysis study of 799 cases, reported no statistically significant difference in major and minor complications between the two approaches, except for facial nerve and chorda tympani injuries, favoring SMA. 20 Migirov et al 21 operated 300 cases of CI and reported a rate of 3% major complications and 25.7% minor complications.…”
Section: Discussionmentioning
confidence: 98%
“…19 Xu et al, 20 in a meta-analysis study of 799 cases, reported no statistically significant difference in major and minor complications between the two approaches, except for facial nerve and chorda tympani injuries, favoring SMA. 20 Migirov et al 21 operated 300 cases of CI and reported a rate of 3% major complications and 25.7% minor complications. 21 Júnior et al, 8 in a study of 250 cases, reported 13 cases (5.2%) of major postoperative complications and 20 cases (8%) of minor complications.…”
Section: Discussionmentioning
confidence: 98%
“…Xu et al found major complication rates of 4.48% and 7.76% after cochlear implantation through suprameatal approach and mastoidectomy with posterior tympanotomy approach respectively. 45 The most common complications reported in the pediatric ABI studies included CSF leak and mild/transitory cerebellar edema, which occurred in up to 8.5% and 9.2% of patients, respectively. The prevalence of CSF leaks is comparable to the leak rate following primary vestibular schwannoma surgery via retrosigmoid craniotomy (10.6%) 46 and lower than that in NF2 adults who received an ABI (17.6%, 6 of 34).…”
Section: Discussionmentioning
confidence: 98%
“…A meta‐analysis by Xu et al . revealed no difference in postoperative complication rates between SMA and MPTA patients.…”
mentioning
confidence: 96%